Ultrahigh cycle fatigue deformation of polycrystalline NiTi micropillars. (October 2021) - Hua, Peng; Lin, Hongyang; Sun, Qingping
Abstract: Bulk polycrystalline superelastic NiTi shape memory alloy usually has limited fatigue lives. Here we show that polycrystalline superelastic NiTi micropillars under compressive stresses of 1 GPa and 1.5 GPa can endure over 10 8 phase transition cycles, two orders of magnitude larger than the reported fatigue life of 1.12 × 10 6 cycles under 1.2 GPa of bulk polycrystalline NiTi pillars with a similar grain size. The dominant crack nucleation and propagation mechanisms in bulk samples are suppressed in the micropillars due to the elimination of internal micro-voids and surface scratches in the small physical dimensions. Transformation-induced dislocations and the associated residual martensites are constrained at the nanoscale and do not lead to crack nucleation. The research reveals the importance of sample dimensions in bringing changes in the fatigue performance and mechanisms of the material. The observed sample size effects can be exploited to obtain ultrahigh fatigue life at the microscale. Graphical abstract: Image, graphical abstract